2018
DOI: 10.3390/met8040240
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Control of Rare Earth Metals and Their Behaviors in the Industrial Practical Production of Q420q Structural Bridge Steel Plate

Abstract: Rare earth (RE) addition can refine and change the shape/distribution of inclusions in steel to improve its strength and toughness. In this paper, the control of RE, specifically Ce and La, and their behaviors in the practical industrial production of high-strength structural steel with 420 MPa yield strength were studied. In particular, the interactions between RE and Al, Nb, S, O were investigated, with the aim of improving the steel toughness and welding performance. The impact energy of the plate with RE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The major portion of these papers is focused on the mechanisms of microstructure evolution and the mechanical properties of metallic materials subjected to various thermo-mechanical, deformation, or heat treatments [1][2][3][4][5][6][7][8][9][10][11][12]. Another large portion of the studies is aimed on the elaboration of alloying design of advanced steels and alloys [13][14][15][16]. The changes in phase content, transformation, and particle precipitation and their effect on the properties are also broadly presented in this collection [17][18][19][20][21].…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major portion of these papers is focused on the mechanisms of microstructure evolution and the mechanical properties of metallic materials subjected to various thermo-mechanical, deformation, or heat treatments [1][2][3][4][5][6][7][8][9][10][11][12]. Another large portion of the studies is aimed on the elaboration of alloying design of advanced steels and alloys [13][14][15][16]. The changes in phase content, transformation, and particle precipitation and their effect on the properties are also broadly presented in this collection [17][18][19][20][21].…”
Section: Contributionsmentioning
confidence: 99%
“…Those readers interested in structural steels may learn much from comprehensive investigations of microstructural changes and their effect on mechanical properties caused by plastic working and heat treatment of diverse steel types [2,7,8,10,12,15,16,[19][20][21][22]. Two of these papers [7,12] present experimental/simulation results of mechanical behavior of high-Mn TWIP steels, which have recently aroused a great interest among material scientists and engineers because of outstanding strengthductility combination inherent in such steels.…”
Section: Contributionsmentioning
confidence: 99%
“…At present, many researchers have indicated that adding suitable RE elements can improve the cryogenic toughness index, mainly by refining grains, purifying steel matrix, and changing the morphology of inclusions. [ 1–12 ] Wu et al [ 13 ] investigated RE element on the strength and toughness of Nb‐alloyed steel. The results indicated that the mixed La + Ce RE compound is promising to replace the Nb element to improve the cryogenic toughness of the product.…”
Section: Introductionmentioning
confidence: 99%
“…However, for Al-killed steel, some enterprises also carry out Ca treatment after rare earth addition in industrial production. 14) Therefore, this work was undertaken to reveal evolution of inclusions after Ce addition and Ca treatment in RH refining process of Al-killed steel. A SEM equipped with and EDS was employed to characterize the inclusions, and thermodynamic calculation was performed to clarify the modification process of oxide inclusions.…”
Section: Introductionmentioning
confidence: 99%